Economic, social and technical considerations determining investments in groundwater in Bangladesh - Johnson, S.H. (1986)
With a total land area the size of the state of Illinois and a population exceeding 90 million, Bangladesh has one of the highest man-land ratios in the world. Blessed with vast river systems but having such a flat topography that large-scale reservoir and gravity surface irrigation systems are not feasible, Bangladesh has been forced to turn to groundwater as a source for dry season irrigation water. Initial investments were in low-lift pumps but now the Government of Bangladesh (GOB) is encouraging investment in hand pumps, shallow tubewells and deep tubewells as sources for additional water for irrigation. However, to date utilization rates have been far below those predicted by national planners.